1996
DOI: 10.2166/wst.1996.0391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and alkalinity on sulfur-denitrification in a biological granular filter

Abstract: Two laboratory-scale biological filters were operated to investigate the effects of alkalinity and pH on removal of nitrate and nitrite in sulfur denitrification filter processes. The concentration of sodium bicarbonate in the feed media was changed from 120 to 240 mg/l during about 3 months in a filter (Run A). The other filter was initially fed with 300 mg/l and then with 240 mg/l (Run B). The performance of the filter was monitored by measuring pH, nitrate, nitrite, sulfate, alkalinity, and thiosulfate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 0 publications
0
24
0
3
Order By: Relevance
“…Similar results were obtained in case of nitrification by Glass and Silverstein (1998), who observed a significantly increased nitrite accumulation (250, 500 or 900 mg NO − 2 -N L −1 ) in sequencing batch reactors when mixed liquid pH was increased during nitrification (pH 7.5, 8.5 or 9.0 respectively). On the other hand, Furumai et al (1996) found an accumulation of nitrite at pH-values lower than 7.4 or at low alkalinity in a denitrifying granular filter.…”
Section: Surmaczmentioning
confidence: 88%
“…Similar results were obtained in case of nitrification by Glass and Silverstein (1998), who observed a significantly increased nitrite accumulation (250, 500 or 900 mg NO − 2 -N L −1 ) in sequencing batch reactors when mixed liquid pH was increased during nitrification (pH 7.5, 8.5 or 9.0 respectively). On the other hand, Furumai et al (1996) found an accumulation of nitrite at pH-values lower than 7.4 or at low alkalinity in a denitrifying granular filter.…”
Section: Surmaczmentioning
confidence: 88%
“…3 Development of the kinetic model According to literature [20], nitrate reduction could be represented by a Monod-type equation while nitrite reduction can be described by Haldane-type kinetics. The accumulation of nitrite has also been reported as a kinetic affecting factor which could depend of the pH [21], the S/N ratio used [22][23], the competition for each electron acceptor (nitrite or nitrate) [24], etc. In this work none of these considerations were included in the kinetic model since in a previous study [16] it was observed that the factor affecting the progress of this process for a constant pH was the denitratation and denitritation kinetics, being this fact related with the biomass present in the culture.…”
Section: Here Tablementioning
confidence: 99%
“…4-7) as well as a Monod-type term to describe thiosulfate oxidation were considered. No elemental sulfur accumulation was included in the model since, as previously referenced [16,21,30], thiosulfate oxidation under anoxic conditions produced directly sulfate as the final product.…”
Section: Modeling Denitritation Kineticsmentioning
confidence: 99%
“…Several studies have investigated thiosulphate as an electron donor [73,74]. The average observed yield was 0.17 g VSS/g NO 3 -N [57].…”
Section: Reduced Sulphur Compoundsmentioning
confidence: 99%